Taste bud cells of adult mice are responsive to Wnt/β-catenin signaling: implications for the renewal of mature taste cells - Gaillard, Dany (2011)
Wnt/β-catenin signaling initiates taste papilla development in mouse embryos, however, its involvement in taste cell turnover in adult mice has not been explored. Here we used the BATGAL reporter mouse model, which carries an engineered allele in which the LacZ gene is expressed in the presence of activated β-catenin, to determine the responsiveness of adult taste bud cells to canonical Wnt signaling. Double immunostaining with markers of differentiated taste cells revealed that a subset of type I, II and III taste cells express β-galactosidase. Using in situ hybridization, we showed that β-catenin activates the transcription of the LacZ gene mainly in intragemmal basal cells that are immature taste cells, identified by their expression of Sonic Hedgehog (Shh). Finally, we showed that β-catenin activity is significantly reduced in taste buds of 25 week-old mice compared to 10 week-old animals. Our data suggest that Wnt/β-catenin signaling may influence taste cell turnover by regulating cell differentiation. Reduced canonical Wnt signaling in older mice could explain in part the loss of taste sensitivity with aging, implicating a possible deficiency in the rate of taste cell renewal. More investigations are now necessary to understand if and how Wnt signaling regulates adult taste cell turnover.